Organizing passenger flows at the station complex - Muratbekov, Beibarys; Вахитова, Лилия; Muratbekova, Gulzhan; Aimanbetov, Nurgeldy (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
This article considers the issue of optimizing passenger traffic at the station complex in modern conditions. The experience and scientific research of foreign scientists from China, Japan and Russia have been studied. Four different ways of organising passengers are discussed, with the most promising and working method revealed to be a comprehensive change in the train schedule and dynamic routing of passengers with absolute blocking. A forecast model in its turn depends on verifiable information, can more or less produce anticipated approaching volume of people, but it appears to be compelling when there are celebrations or understudy occasions. Whereas building a modern stage with a reason of facilitating an exchanging section does relieve the circumstance at the station and security measures considerably. Lastly, the most issue of serving traveler amid the COVID-19 pandemic were taking off strategy from stations and arrangement of travelers to sit separated at a certain distance for shirking of cleansing. In this master’s proposal, the procedures to handle and gauge traveler stream have been regarded, but activities need to be made amid breakdown of trains have not been surveyed.